"Inhibitory Activity Test of White Turmeric (Curcuma zedoaria) Extract Against Escherichia coli Bacteria" - maulidayanti, sharfina; Nafis, Nidhal Mijwan; Situmorang, Ing Mayfa Br; Armawan, Ladyka Viola Aulia (HEALTH SCIENCE & BIOMEDICAL JOURNAL, 2025)
Introduction: Escherichia coli bacteria are microorganisms that are usually found in the digestive tract in both animals and humans. Belonging to the Enterobacteriaceae family, E. coli has a cell size of between 2.0 to 6.0 micrometers by a diameter of 1.1 to 1.5 micrometers. These bacteria are straight rods and They can be found in singular, paired, or in short chains. E. Objective: This study aims to evaluate the inhibition of white turmeric extract (Curcuma zedoaria) against the pathogenic bacteria Escherichia coli, which is one of the causes of gastrointestinal infections or diarrheal diseases. Method: White turmeric extraction was carried out using the maceration method with a 96% ethanol solvent, which was then tested on Escherichia coli bacteria by the Disc diffusion method, using paper discs that had been soaked in various concentrations of onion extract (15%, 25%, 50%). The inhibition zones formed around the disc are observed and measured to determine the effectiveness of inhibition. Result: Based on research on the inhibitory effect of white turmeric extract on the growth of Escherichia coli bacteria, a concentration of 15% resulted in an average diameter of 7.1 mm (resistant), 25% resulted in a diameter of 9.3 mm (resistant), and 50% resulted in a diameter of 11.3 mm (resistant) on Escherichia coli bacteria. Conclusion: The conclusion of this study is that the more effective concentration to inhibit the growth of Escherichia coli bacteria is at 50% concentration.